2011
DOI: 10.15288/jsad.2011.72.701
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Adolescent Drinking and Adult Violence: Evidence From a Longitudinal Study of Urban African Americans

Abstract: ABSTRACT. Objective: This study examined the relationship between adolescent alcohol use and adult violence from a developmental perspective, specifi cally whether frequent adolescent drinking predicts adult violence once shared risk factors are taken into account through propensity score matching. The research considered multiple types of violence, including assault, robbery, and suicidal behavior, as well as other types of offending. It tested whether educational attainment and adult alcohol use and problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 63 publications
(64 reference statements)
3
16
0
3
Order By: Relevance
“…While our heavy drinking variable is not a perfect measure of a snare, it does resonate with the spirit of what Moffitt was referring to when she discussed events or addictions that can catapult people into further crime. Moreover as others have noted in the literature (Green, Doherty, Zebrak, & Ensminger, 2011;Laub & Sampson, 2003;Sampson & Laub, 1993;Schroeder, Giordano, & Cernkovich, 2007), heavy drinking is a highly complicating factor that may discourage or at least hinder desistance. Similarly, while the CSDD did not measure heavy drinking prior to age 18, the data did contain responses to items querying the males at both ages 14 and 16 if they had previously drank in a pub.…”
Section: Discussionmentioning
confidence: 94%
“…While our heavy drinking variable is not a perfect measure of a snare, it does resonate with the spirit of what Moffitt was referring to when she discussed events or addictions that can catapult people into further crime. Moreover as others have noted in the literature (Green, Doherty, Zebrak, & Ensminger, 2011;Laub & Sampson, 2003;Sampson & Laub, 1993;Schroeder, Giordano, & Cernkovich, 2007), heavy drinking is a highly complicating factor that may discourage or at least hinder desistance. Similarly, while the CSDD did not measure heavy drinking prior to age 18, the data did contain responses to items querying the males at both ages 14 and 16 if they had previously drank in a pub.…”
Section: Discussionmentioning
confidence: 94%
“…Adolescent substance use, therefore, may set boys on a long-term course of psychological distress. Previous research with the Woodlawn population found unemployment to be a consequence of heavy adolescent substance use (Green and Ensminger, 2006; Green et al, 2011), which may be the mechanism driving the long-term association between adolescent substance use and adult psychological distress. Previously, unemployment was found to be particularly relevant in the interrelationship between psychological distress and substance use for African American men (Brunswick et al, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…Nos estudos longitudinais (n = 8), o tempo de acompanhamento dos sujeitos envolvidos, no geral, variou de 1 a 14 anos, exceto o estudo de Green et al 24 , que acompanhou indivíduos por 36 anos. A vitimização como variável independente foi adotada por 05 autores 9,11,[25][26][27] (Tabela 3).…”
Section: Resultsunclassified
“…Isso pode influenciar nos resultados encontrados. Por exemplo, Rudatsikira et al 29 agruparam as variáveis consumo de álcool, tabaco e maconha numa única variável (uso de substâncias), o que impossibilita fazer conclusões sobre a influência do consumo de álcool isoladamente 24 . Já o estudo de Cisler et al 11 agrupou a violência física com a violência sexual e o testemunho de episódios violentos.…”
Section: Discussionunclassified